(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
ABSTRACT The research aims to analyze the value chain of dairy products in Iraq (Abu Ghraib/Study Case) factories for the year 2022, where value chain rings are identified to discuss and track the most important determinants and problems in the value chain rings of dairy products and their basic and secondary activities, as well as calculate the value added of the products by subtracting the total revenues of products from their variable costs. Research data were collected for the period 2022. Preliminary information and data from its field sources and personal interviews were collected through a questionnaire prepared for this purpose for each level of chain loop from suppliers, producers, marketers and consumers. Data was collected on production, costs, profits and revenues. The estimated results indicated that variable costs accounted for the largest share of total dairy costs in the research sample at 83.8% of total costs due to the cost of butter and free fat (9358) thousand dinars, ranked first among variable cost paragraphs 36.1% of total variable costs, while fixed costs accounted for 16.2% of total costs. Research results also found that the total value added of production in Abu Ghraib factories was (4687230.46) Dinars. The most important conclusion is that the analysis of the value chain of Pan Abu Ghraib dairy products is the high variable costs resulting in higher total costs of dairy production. This is negatively reflected in the market produced quantities. The most important recommendations of the research were to reduce the variable costs of all the value chain as well as to reduce the import of dairy products from abroad to support the local product and increase market share.